New Trends in Databases and Information Systems - Pechenizkiy, Mykola; Wojciechowski, Marek; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Database and information systems technologies have been rapidly evolving in several directions over the past years. New types and kinds of data, new types of applications and information systems to support them raise diverse challenges to be addressed. The so-called big data challenge, streaming data management and processing, social networks and other complex data analysis, including semantic reasoning into information systems supporting for instance trading, negotiations, and bidding mechanisms are just some of the emerging research topics. This volume contains papers contributed by six workshops: ADBIS Workshop on GPUs in Databases (GID 2012), Mining Complex and Stream Data (MCSD'12), International Workshop on Ontologies meet Advanced Information Systems (OAIS'2012), Second Workshop on Modeling Multi-commodity Trade: Data models and processing (MMT'12), 1st ADBIS Workshop on Social Data Processing (SDP'12), 1st ADBIS Workshop on Social and Algorithmic Issues in Business Support (SAIBS), and the Ph.D. Consortium associated with the ADBIS 2012 conference that report on the recent developments and an ongoing research in the aforementioned areas.
Part I GPUs in Databases -- Part II Mining Complex and Stream Data -- Part III Ontologies meet Advanced Information Systems -- Part IV Modeling Multi-commodity Trade: Data models and processing -- Part V Social Data Processing -- Part VI Social and Algorithmic Issues in Business Support -- Part VII Ph.D. Consortium.
Keywords: Engineering; Database management; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Database Management